Using earthquakes to uncover the Earth's inner secrets: interactive exhibits for geophysical education - C. Nostro (Advances in Geosciences, 2005)
The Educational & Outreach Group (E&O Group) of the Istituto Nazionale di Geofisica e Vulcanologia (INGV) designed a portable museum to bring on the road educational activities focused on seismology, seismic hazard and Earth science. This project was developed for the first edition of the Science Festival organized in Genoa, Italy, in 2003. The museum has been mainly focused to school students of all ages and explains the main topics of geophysics through posters, movie and slide presentations, and exciting interactive experiments. This new INGV museum has been remarkably successful, being visited by more than 8000 children and adults during the 10 days of the Science Festival. It is now installed at the INGV headquarters in Rome and represents the main attraction during the visits of the schools all year round.